Use of benzo analogs to enhance antimycotic activity of strobilurin for control of aflatoxigenic fungal pathogens - Kim, Jong H.; Mahoney, Noreen; Chan, Kathleen L.; Campbell, Bruce C.; Haff, Ronald P.; Stanker, Larry H. (Frontiers in Microbiology, 2014)
The aim of this study was to examine two benzo analogs, octylgallate (OG) and veratraldehyde (VT), as antifungal agents against strains of Aspergillus parasiticus and A. flavus (toxigenic or atoxigenic). Both toxigenic and atoxigenic strains used were capable of producing kojic acid, another cellular secondary product. A. fumigatus was used as a genetic model for this study. When applied independently, OG exhibits considerably higher antifungal activity compared to VT. The minimum inhibitory concentrations (MICs) of OG were 0.3 - 0.5 mM, while that of VT were 3.0 - 5.0 mM in agar plate-bioassays. OG or VT in concert with the fungicide kresoxim methyl (Kre-Me; strobilurin) greatly enhanced sensitivity of Aspergillus strains to Kre-Me. The combination with OG also overcame the tolerance of A. fumigatus mitogen-activated protein kinase (MAPK) mutants to Kre-Me. The degree of compound interaction resulting from chemosensitization of the fungi by OG was determined using checkerboard bioassays, where synergistic activity greatly lowered MICs or minimum fungicidal concentrations. However, the control chemosensitizer benzohydroxamic acid, an alternative oxidase inhibitor conventionally applied in concert with strobilurin, did not achieve synergism. The level of antifungal or chemosensitizing activity was also “compound - strain” specific, indicating differential susceptibility of tested strains to OG or VT, and/or heat stress. Besides targeting the antioxidant system, OG also negatively affected the cell wall-integrity pathway, as determined by the inhibition of Saccharomyces cerevisiae cell wall-integrity MAPK pathway mutants. We concluded that certain benzo analogs effectively inhibit fungal growth. They possess chemosensitizing capability to increase efficacy of Kre-Me and thus could reduce effective dosages of strobilurins and alleviate negative side effects associated with current antifungal practices. OG also exhibits moderate antiaflatoxigenic activity.